2021
DOI: 10.1038/s41419-021-03408-1
|View full text |Cite
|
Sign up to set email alerts
|

SCA-1 micro-heterogeneity in the fate decision of dystrophic fibro/adipogenic progenitors

Abstract: The term micro-heterogeneity refers to non-genetic cell to cell variability observed in a bell-shaped distribution of the expression of a trait within a population. The contribution of micro-heterogeneity to physiology and pathology remains largely uncharacterised. To address such an issue, we investigated the impact of heterogeneity in skeletal muscle fibro/adipogenic progenitors (FAPs) isolated from an animal model of Duchenne muscular dystrophy (DMD), the mdx mouse. FAPs play an essential role in muscle hom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 66 publications
0
20
0
2
Order By: Relevance
“…We thus decided to focus our analysis on this cell population that we found overrepresented in DMD muscles compared to WT. In comparison, such a large increase in cell number has never been observed in the mdx mouse model, in which the FAP number was reported to be only slightly increased [ 20 ]. Next, we targeted the scRNAseq analysis by focusing on the transcriptomic changes between WT and R-DMDdel52 samples, and identified COMP as a crucial extracellular matrix protein that could be used as a specific biomarker of muscle fibrosis, as previously done for liver, lung, and skin diseases follow-up [ 4 , 17 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…We thus decided to focus our analysis on this cell population that we found overrepresented in DMD muscles compared to WT. In comparison, such a large increase in cell number has never been observed in the mdx mouse model, in which the FAP number was reported to be only slightly increased [ 20 ]. Next, we targeted the scRNAseq analysis by focusing on the transcriptomic changes between WT and R-DMDdel52 samples, and identified COMP as a crucial extracellular matrix protein that could be used as a specific biomarker of muscle fibrosis, as previously done for liver, lung, and skin diseases follow-up [ 4 , 17 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is a common hallmark of several congenital muscular dystrophies, and notably, FAPs are pathologically dysregulated in most of them (Figure 4). These include mouse models of Collagen VI- (Noguchi et al, 2017;Mohassel et al, 2018), human DMD (Uezumi et al, 2014) and mouse models of DMD (Box 1) (Uezumi et al, 2011;Mozzetta et al, 2013;Lemos et al, 2015;Contreras et al, 2016Contreras et al, , 2020Ieronimakis et al, 2016;Kopinke et al, 2017;Mázala et al, 2020;Reggio et al, 2020;Giuliani et al, 2021), Facioscapulohumeral dystrophy (FSHD) (Bosnakovski et al, 2017(Bosnakovski et al, , 2020, Limb-girdle muscular dystrophy (LGMD) (Hogarth et al, 2019), and ALS neuromuscular disease (Gonzalez et al, 2017;Madaro et al, 2018). Increased muscle fibrosis and FAP expansion also occur after single and repeated cycles of intramuscular BaCl 2 , notexin, cardiotoxin, or glycerol administrations (Uezumi et al, 2010;Dadgar et al, 2014;Pessina et al, 2014;Contreras et al, 2016Contreras et al, , 2020Theret et al, 2021), vastus medialis muscles of compromised knee osteoarthritis patients (Ikemoto- Uezumi et al, 2017), human anterior cruciate ligament injuries (Fry et al, 2017), induced hindlimb ischemia (Santini et al, 2020), degenerated muscles of type 2 diabetic patients (Farup et al, 2020), obesity-mediated diaphragm dysfunction of chronic high-fat diet-fed mice (Buras et al, 2019), and surgical muscle traumas including denervation and laceration (Brandan et al, 1992;Pessina et al, 2014;Contreras et al, 2016;…”
Section: Fibro-adipogenic Progenitors As Pathological Drivers Of Muscmentioning
confidence: 99%
“…FAPs cultured in vitro can spontaneously differentiate into fibroblasts or adipocytes [ 15 , 17 ]. Their fibrogenic differentiation can be stimulated by adding transforming growth factor-β (TGF-β) to the medium, while their adipogenic differentiation can be promoted by a medium containing insulin, 3-isobutyl-1-methylxanthine and dexamethasone [ 33 35 ]. Lineage tracing experiments confirmed that this multipotent capacity is also observed in vivo .…”
Section: Faps Characteristicsmentioning
confidence: 99%
“…Two subpopulations of FAPs, the Sca1-low/CD34-low and Sca1-high/CD34-high subsets, which are predominantly found in non-injured and injured wild-type muscles, respectively, are both found alongside within mdx muscles [ 34 ]. The Sca1-high subpopulation proliferate faster than the Sca1-low subpopulation and are predisposed to differentiate into adipocytes [ 33 ]. Similarly, there is the emergence of a subpopulation of PDGFRα-low FAPs expressing high levels of fibroblast associated genes ( TGFb1 , Col1a1 and CTGF ) in the skeletal muscles of mdx mice [ 66 ].…”
Section: Faps In Muscular Dystrophiesmentioning
confidence: 99%